Tri-process model of interpersonal mindfulness: theoretical framework and study protocol - Khoury, Bassam; Manova, Viktoriya; Adel, Lena; Dumas, Guillaume; Lifshitz, Michael; Vergara, Rodrigo C.; Sekhon, Harmehr; Rej, Soham (Frontiers in Psychology, 2023)
According to the Center for Disease Control and Prevention, over 14% of the US population practice mindfulness meditation. The effects of mindfulness training on physical and mental health have been consistently documented, but its effects on interpersonal relationships are not yet fully understood or investigated. Interpersonal relationships play a crucial role in the wellbeing of individuals and society, and therefore, warrants further study. The aim of this paper is to present a tri-process theoretical model of interpersonal mindfulness and a study protocol to validate the proposed model. Specifically, according to the proposed model, mindfulness meditation training increases the self-awareness, self-regulation, and prosociality of those receiving the training, which ameliorates the quality of interpersonal interactions and the socioemotional support provided to other individuals. Finally, better socioemotional support increases the support receiver’s ability to regulate their emotions. Using a multiphasic longitudinal design involving 640 participants randomized into 480 dyads, the proposed protocol aims to validate the tri-process model and to investigate its mechanisms of actions. The proposed study has important theoretical and social implications and will allow devising new and more effective interpersonal mindfulness programs with applications in multiple fields.